The implication of capital structure towards the profitability performance of PN17 companies / Wan Nor Alia Wan Mohd Saleh - Wan Mohd Saleh, Wan Nor Alia (Faculty of Business Management, 2017)
This research aims at investigating the effect of capital structure on the profitability performance of PN17 companies that listed in Bursa Malaysia. This study is to explore the impact of three variables, namely short-term debt ratio, long-term debt ratio, and total debt ratio on the return on equity by using balance panel data set of listed companies between 2010 until 2015. Panel data methodology was employed and White Cross-section regression was used to estimate the coefficient of explanatory variables. The result indicated that the profitability performance are negatively affected by short-term debt ratio and total debt ratio. The result obtained might indicate thatthe firm might funding their activities by using the Pecking order theory, which is based on the idea that the companies will use their internal financing sources first to operate their activities (Ahmed Sheikh andWang, 2011). When a company probably become bankruptcy and distress, an increasedin debt can cause a higher total agency costs that effectingto a negative result on firm profitability (Dawar,2014). The result acquired from this study also shows that only 2.28 percent inReturn on Equity were influencedby short-term debt ratio, long-term debt ratio and total debt ratio.Whereas, the remaining are determine by other factors, such as economic, and sales performance